Decolonizing Theological Education: Learning from Latinx, Womanist, and Asian Voices for Transformative Pedagogy Atando Cabos: Latinx Contributions to Theological Education, ElizabethConde‐Frazier, Eerdmans, 2021 (ISBN 978‐0‐8028‐7901‐1), vii + 151 pp., pb 19.99Notes of a Native Daughter: Testifying in Theological Education, KeriDay, Eerdmans, 2021 (ISBN 978‐0‐8028‐7882‐3), viii + 144 pp., pb 19.99Attempt Great Things for God: Theological Education in Diaspora, Chloe T.Sun, Eerdmans, 2020 (ISBN 978‐0‐8028‐7842‐7), vi + 142 pp., pb 19.99. Issue 1 (9th April 2022) - Dominiak, Paul
Abstract: Theological education—and society more broadly—stands critically 'between the times'. Contemporary theological education exists between traditional modes of formation implicitly shaped by western colonialism and an uncertain future occasioned by seismic shifts around funding, admissions, ecologies of formation, and globalization. This 'between the times' moment both threatens the survival of theological education institutes and also unveils the historic and ongoing complicity of theological education in the wider racist colonial legacies of white privilege and hegemony. The same 'in between' moment also proffers to theological education the possibility to embrace diverse voices and transformative pedagogies within theological education as part of decolonization and decolonizing the curriculum. Embracing decolonizing theology will both save the soul of theological education and may help it survive through embracing collaborative, creative, and intersectional models of education that meet pragmatic needs as well as moral imperatives. This article explores three publications by Elizabeth Conde‐Frazier, Keri Day, and Chloe Sun that offer Latinx, womanist, and Asian theological perspectives on decolonizing theology in this 'between the times' moment of theological education. Setting out first the ecclesial and then the wider political contexts of these three works, the article examines how they imagine new decolonized possibilities for theological education. Following Graham Ward, the article develops how all three authors in their own ways argue that decolonizing theology and theological education entails 'provincializing' the (white) western context as normative, 'translating' or 'transplanting' theology back into culturally authentic discourses that contend meaning and deconstruct white power, and positively 'affirming' the varied cultural identities in which theological meaning is located.